Análisis socioeconómico del sistema de comercialización del maíz producido en el cantón Pedro Carbo, provincia del Guayas - Rodríguez Lara, Erika Stefanía (2021)
Ecuador is a country that has valuable geographical areas for agricultural production, which is represented in the economic contribution that agriculture generates in the country's GDP. The Pedro Carbo canton, located in the Guayas province, is a town whose main activities are Agriculture, commerce and livestock, and one of the star products is corn. Although it is true, the Pedro Carbo canton is one of the main producers of hard yellow corn in the area, it is also true that the people who dedicate themselves to this activity have many limitations that prevent them from obtaining an economic benefit according to the work they do. they already realize the quality of the product they sell..........